Heat-induced proteomic changes in anthers of contrasting rice genotypes under variable stress regimes - Kumar, Ritesh; Ghatak, Arindam; Goyal, Isha; Sarkar, Neelam K.; Weckwerth, Wolfram; Grover, Anil; Chaturvedi, Palak (Frontiers in Plant Science, 2023)
Heat stress drastically affects anther tissues resulting in poor plant fertility, necessitating an urgent need to determine the key proteome regulation associated with mature anther in response to heat stress. We identified several genotype-specific protein alterations in rice anthers of Moroberekan (Japonica, heat sensitive), IR64 (Indica, moderately heat tolerant), and Nagina22 (Aus, heat tolerant) in the short-term (ST_HS; one cycle of 42°C, 4 hours before anthesis) and long-term (LT_HS; 6 cycles of 38°C, 6 hours before anthesis) heat stress. The number of proteins identified in control and heat-stressed anthers was higher in Nagina22 than in IR64 and Moroberekan. The proteins upregulated in long-term heat stress in Nagina22 were enriched in biological processes related to unfolded protein binding and carboxylic acid metabolism, including amino acid metabolism. Similarly, Nagina22 anthers were enriched in proteins associated with vitamin E biosynthesis and GTPase activator activity in short-term heat stress. In contrast, downregulated proteins were related to ribosomal proteins. The regulations of different Hsp20 and DnaJ were genotype-specific. Overall, the heat response in Nagina22 was associated with its capacity for adequate metabolic control and cellular homeostasis, which may be critical for its higher reproductive thermotolerance. This study improves our understanding of thermotolerance mechanisms in rice anthers during anthesis and also lays a foundation for breeding thermotolerant varieties via molecular breeding.